Humanitarian Corridors a New Approach To Addressing Humanitarian Crises - Name-in, Somporn; Suksabay, Chatree (Thai Social Science Journal, 2026)
This article analyzes the dynamics of "Humanitarian Corridors" as a strategic mechanism for addressing complex crises, moving beyond descriptive accounts to a critical synthesis based on International Relations theories and humanitarian principles. The study argues that humanitarian corridors are not merely logistical routes but contested spaces negotiating between state sovereignty and human rights. By examining the application of these corridors in both armed conflicts and natural disasters, the article highlights a conceptual expansion towards "Humanitarian Logistics Corridors." The analysis reveals that failures in cases like Syria and the Rohingya crisis stem from the "politicization of aid," where sovereign states perceive humanitarian access as a security threat. Conversely, success in other contexts relies on integrating technologies such as GIS and AI for decision-making support. Finally, the article proposes shifting focus from temporary emergency measures to the "Humanitarian-Development Nexus," ensuring that the infrastructure established for corridors serves as a foundation for long-term community resilience and sustainable recovery.